Use of recommended posttreatment services for adolescent and young adult survivors of Hodgkin lymphoma. Issue 9 (8th January 2019) - Hahn, Erin E.; Wu, Yi‐Lin; Munoz‐Plaza, Corrine E.; Garcia Delgadillo, Jazmine; Cooper, Robert M.; Chao, Chun R.
Abstract: Background: Hodgkin lymphoma (HL) is a leading cancer diagnosis for adolescents and young adults (AYAs), with an overall 5‐year survival rate of >80%. However, to the authors' knowledge, little is known regarding posttreatment patterns of care. In the current study, the authors characterized the use of guideline‐recommended services in a cohort of AYA survivors of HL in Kaiser Permanente Southern California. Methods: Patients with HL who were diagnosed between ages 15 and 39 years between 2000 and 2010 were identified. The authors calculated the number of patients who received recommended short‐term care within 2 years after treatment cessation for those who remained enrolled and alive from 2001 through 2015. Use of recommended late‐effects screening for breast cancer and cardiovascular disease was examined. Logistic regression was used to evaluate the association between receipt of recommended care and patient, cancer, and treatment characteristics. Results: A total of 354 patients were identified, with a mean age at the time of diagnosis of 26 years (standard deviation, 6.9 years). Approximately 12% of patients had stage I disease, 59% had stage II disease, 17% had stage III disease, and 13% of patients had stage IV disease. Nearly all patients received chemotherapy (95%), 51% received radiotherapy, and 5% received care from a pediatric oncologist. Overall, approximately 49% of patients received recommended short‐term care. Of those patients eligible for cardiovascular screening at 10 years posttreatment (60 patients), 53% received at least 1 screening. Of those patients eligible for breast cancer screening (21 patients), approximately 50% underwent at least 1 screening. Regression results indicated that those patients treated by a pediatric oncologist were >3 times as likely to receive recommended short‐term care. Conclusions: The results of the current study highlight gaps in the delivery of posttreatment care to AYA survivors of HL. By determining areas in need of improvement, these findings can guide the development of tailored interventions with which to improve care. Abstract : Adolescents and young adults who are treated for Hodgkin lymphoma may not receive optimal posttreatment care. By determining areas in need of improvement, the findings of the current study can guide the development of tailored interventions to improve care delivery.